The Early Bronze Age of Tell el-Hesi and its environs From Petrie’s initial discovery to today’s understanding - Ludvik, Geoffrey E.; Blakely, Jeffrey A. 1952- (2020)
While excavating at Tell el-Hesi in the spring of 1890, W. M. F. Petrie discovered the Early Bronze Age, which was further explored by F. J. Bliss over the next two years. Soon other large and important sites in Palestine were excavated and they came to define the Early Bronze Age while Hesi was almost forgotten. Starting in 1970, the Joint Archaeological Expedition to Tell el-Hesi returned to the site and as part of that work they excavated additional Early Bronze Age remains there. The Joint Expedition identified a large one-period EBIIIA city, but most of this work remains unpublished. Today, we recognize a variety of unique aspects that define the EBIIIA site and the region. This article discusses the major changes that have taken place in the interpretation of Tell el-Hesi and its surroundings in the 3rd millennium BCE from Petrie to the present. The authors contextualize Tell el-Hesi in the recent debates on the nature of EBII-III in the Southern Levant and present a summary of results from surveys, unpublished excavation records, and insights into the region developed over the past several decades. These different lines of evidence from EBIIIA Hesi are then synthesized to articulate our current interpretative paradigm.